Organic Nitrogen in Precipitation: Real Problem or Sampling Artefact? - J.N. Cape; A. Kirika; A.P. Rowland; D.R. Wilson; T.D. Jickells; S. Cornell (The Scientific World Journal)
Published observations of organic nitrogen (N) compounds in precipitation go back almost a century. Several different methods have been used to measure both the total and ionic concentrations of N. There is therefore some uncertainty as to whether reported organic N is real, or simply the result of uncertainties in chemical analyses or inadequate sampling methods. We found that the materials from which the collector was made (polypropylene, steel, or glass) had no significant effect on the composition of dissolved organic N (DON). The use of a biocide was found to be very important during sampling and storage of samples before analysis. We set up a network of seven collectors across the U.K., from the Cairngorms to Dorset, all operating to the same protocol, and including a biocide. Samples were analysed centrally, using proven methods. Over 6 months, organic N contributed about 20% to the total N in U.K. precipitation, but with a large variation across the country. This means that current estimates of wet deposited N to the U.K., which are based only on the ammonium and nitrate concentrations, are too small. Organic N is not an artefact, but a real problem that needs to be addressed.